Steamship Disenchantment<subtitle>Chronotopes of Sea Adventure in Nordahl Grieg’s Skibet gaar videre</subtitle> - Dean Krouk (Edda)
This article analyzes Nordahl Grieg’s Skibet gaar videre (1924) as a maritime novel from the age of steamships. It explains the novel’s “maritime world picture” (Søren Frank) as a kind of disenchantment connected to the steamship. In addition, it analyzes the novel’s moments of re-enchantment that are connected to sailing ships and sea animals. The article is structured around several genre-typical chronotopes of sea adventure narrative, which help to explain the young Grieg’s aesthetic and ideological relations to the novel of the sea.